Monitoring biochemical markers during pharmacotherapeutic follow-up of type 2 diabetic patients - Luciana Macatrão Nogueira Nunes; Thiago Moreira de Olinda; Marta Maria França Fonteles; Miguel Nasser Hissa; Silvânia Maria Mendes de Vasconcelos; Daniel Freire de Sousa; Maria Goretti Rodrigues de Queiroz (São Paulo State University (UNESP), 2012)
Loss of the modulatory role of the endothelium may be an important factor in the development of diabetic vascular diseases such as cardiac, cerebral and peripheral vascular disease, as evidenced by changes in the serum lipid profile: increased triglycerides (TG), total lipoprotein cholesterol (TC) and lowdensity lipoprotein (LDL-C), and reduced highdensity lipoprotein (HDL-C). This article describes a longitudinal intervention study conducted at the Center for Research in Diabetes and Endocrinometabolic Diseases of the Federal University of Ceará (UFC, CE, Brazil), in which 58 patients with type 2 diabetes (DM2) were monitored by recording biochemical parameters during two sessions of laboratory tests, and through monthly interview-based pharmacotherapeutic followup. The study lasted one year and was approved by the human research ethics committee of UFC. The data collected were analyzed with the aid of the program SPSS 11.0. Hypertension was present in 54.4% of patients with DM2, 64% were sedentary and overweight, 44.7% reported having relatives with cardiovascular disease and 59.5% had a family history of diabetes. The serum levels of fasting glucose, TG, TC and LDL-C and the systolic and diastolic blood pressure were reduced after the active follow-up and monitoring of patients. This result reinforces the importance of the role of the pharmacist in the control of biochemical parameters, improvement of patients' quality of life and prevention of complications.